Modified lithium iron manganese phosphate material and preparation method thereof, positive electrode material and lithium ion battery

By modifying grafting with hydrophobic agents in lithium manganese iron phosphate materials and introducing niobium or aluminum doping to form core-shell structures and superlattice structures, the problems of material stability and electrochemical performance are solved, and higher The electron conductivity and lithium ion diffusion coefficient improve the electrochemical performance and cycle life of the battery.

CN119230779AActive Publication Date: 2024-12-31HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411347635.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate materials have poor structural stability, low electronic conductivity, low lithium ion diffusion coefficient and prone to exceed the standard of moisture during the preparation process, resulting in poor electrochemical performance.

Method used

Use hydrophobic agent to modify and graft the carbon source to form a core-shell structure that is tightly wrapped with lithium manganese iron phosphate, and introduces niobium or aluminum doping elements into the material to improve the hydrophobicity and conductivity of the material and form an orderly super Lattice structure.

Benefits of technology

The structural stability, electronic conductivity and lithium ion diffusion coefficient of lithium manganese iron phosphate materials have been significantly improved, the electrochemical performance and cycle life have been improved, and the problem of moisture exceeding the standard is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230779A_ABST
    Figure CN119230779A_ABST
Patent Text Reader

Abstract

The invention provides a modified lithium iron manganese phosphate material and a preparation method thereof, a positive electrode material and a lithium ion battery. The modified lithium manganese iron phosphate material comprises an inner core and a hydrophobic carbon layer coated on the surface of the inner core, and the inner core comprises a lithium manganese iron phosphate material doped with niobium and / or aluminum; the raw material of the hydrophobic carbon layer is a carbon source modified by a specific hydrophobic agent. The hydrophobic agent is adopted to modify and graft the carbon source, so that a stable core-shell structure can be formed, and the stability of the lithium manganese iron phosphate structure can be effectively improved; the hydrophobic agent grafted on the surface of the carbon source and a carbon chain structure provided by the carbon source are beneficial to improving the electronic conductivity and conductivity of the lithium manganese iron phosphate material; by doping specific elements, collapse of a lithium manganese iron phosphate crystal structure can be effectively inhibited, and the electronic conductivity of the lithium manganese iron phosphate crystal structure is improved; the hydrophobic property of the lithium manganese iron phosphate material is remarkably improved by the specific type of hydrophobic agent, and the electrochemical performance of the material is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a modified lithium manganese iron phosphate material and a preparation method thereof, a positive electrode material and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high conversion efficiency, high energy density and power density, no memory effect, and long service life. They have become the most mature and widely used battery system. People expect lithium-ion battery materials to have lower costs, higher energy density, and higher safety performance.

[0003] Lithium manganese iron phosphate material (LMFP) is obtained by doping and introducing Mn ions into lithium iron phosphate material (LFP). Since LMFP has a higher operating voltage (up to 4.1V), it has a higher energy density (about 20% higher than LFP) than LFP. The advantages of LMFP such as low cost, high stability and environmental friendliness also make this material have broad development prospects.

[0004] However, the lithium manganese iron phosphate material itself has some disadvantages, such as: Mn 3+ The JT effect causes lattice distortion, which will destroy the structural stability; the electronic conductivity is low (about 1×10 -9 s / cm); the lithium ion diffusion coefficient is low (about 5.1×10 -14 cm 2 / s) and other problems. It is easy to come into contact with air during the processing and preparation process, resulting in excessive moisture. The electrochemical properties of lithium-ion batteries, such as charge and discharge performance and cycle efficiency, still need to be improved. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified lithium iron manganese phosphate material and a preparation method thereof, a positive electrode material and a lithium ion battery, so as to solve the problems in the prior art that the lithium iron manganese phosphate material has poor structural stability, low electronic conductivity, low lithium ion diffusion coefficient, and easy excessive moisture during the preparation process, resulting in poor electrochemical performance.

[0006] In order to achieve the above object, according to one aspect of the present invention, a modified lithium manganese iron phosphate material is provided, comprising a core and a hydrophobic carbon layer coated on the surface of the core, wherein the core comprises the lithium manganese iron phosphate material, and its general formula is Li x Fe y Mn 1-y- z M zPO4, 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; M is niobium and / or aluminum; the raw material of the hydrophobic carbon layer is a carbon source modified by a hydrophobic agent; the hydrophobic agent includes one or more of octadecyltrichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyltriethoxysilane, tetraethoxysilane and polyacrylamide. The present invention uses a hydrophobic agent to modify and graft the carbon source, and the hydrophobic carbon source presents a curled shape during the preparation process, tightly wraps the precursor of the lithium manganese iron phosphate material, and forms a stable core-shell structure. The hydrophobic carbon layer can support the overall structure of the lithium manganese iron phosphate, keep its own structure stable and not easily destroyed, which is beneficial to improve the stability of the lithium manganese iron phosphate structure, and can stabilize its own structure and not be easily destroyed in the subsequent crushing process. The carbon chain of the hydrophobic agent is grafted on the surface of the carbon source to form an organic branched chain. In the process of preparing lithium iron manganese phosphate, the carbon source and the branched chain are carbonized. The rich carbon chain structure is conducive to improving the transmission efficiency of electrons, thereby improving the electronic conductivity and electrical conductivity of the lithium iron manganese phosphate material. The modified lithium iron manganese phosphate material of the present invention contains specific doping elements of niobium and / or aluminum. On the one hand, the doping elements can expand the lithium ion diffusion channel and reduce the energy barrier of lithium ion transmission; on the other hand, the addition of doping elements can make the lithium iron manganese phosphate material highly oriented, the grains are slender, and an ordered superlattice structure is formed. The highly oriented grains can effectively inhibit the increase of internal resistance and improve the capacity retention rate of the material. The superlattice structure can also effectively inhibit the collapse of the crystal structure during charging and discharging, forming defects and holes inside the crystal, thereby changing the electronic structure of the material and improving the electronic conductivity of the material. By using a hydrophobic agent to modify the lithium iron manganese phosphate material, a hydrophobic structure can be formed on its surface, which significantly improves the hydrophobicity of the lithium iron manganese phosphate material. This is beneficial to solving the problem of excessive moisture in the lithium iron manganese phosphate material during the preparation process, and can further effectively improve the electrochemical properties of the lithium iron manganese phosphate material.

[0007] Furthermore, the D50 particle size of the modified lithium iron manganese phosphate material is 350 to 420 nm. Since the modified lithium iron manganese phosphate material of the present invention includes a hydrophobic carbon layer, the carbon source molecular chain tightly wraps the precursor of the lithium iron manganese phosphate material, making the particle size of the modified lithium iron manganese phosphate smaller and the carbon layer more compact. On the basis of ensuring the hydrophobicity of the lithium iron manganese phosphate material, by controlling the material particle size within the above-mentioned small particle size range, the transfer path of lithium ions can be more effectively shortened and the transfer speed can be increased, thereby further improving the electrochemical performance of the lithium iron manganese phosphate material.

[0008] Furthermore, the mass ratio of the core to the carbon source is 100:(5.2-6.2). Under the above conditions, the core and the carbon source can cooperate with each other, and under the reduction reaction conditions, the carbon source can tightly wrap the core without affecting the deintercalation of lithium ions, stably support the overall structure of lithium iron manganese phosphate, provide a more sufficient conductive channel, and be more conducive to improving the conductive properties of lithium iron manganese phosphate materials, thereby making the stability, hydrophobicity and electrochemical properties of lithium iron manganese phosphate materials better.

[0009] According to another aspect of the present invention, a method for preparing a modified lithium iron manganese phosphate material is provided, comprising the following steps: step S1, pre-treating a carbon source to obtain a pre-treated carbon source, and performing a first stirring and photochemical reaction on the pre-treated carbon source with a first solvent and a hydrophobic agent to obtain a first mixed solution containing a modified carbon source; step S2, sequentially performing a second stirring and a first grinding on a lithium source, an iron source, a manganese source, a phosphorus source and a second solvent to obtain a second mixed solution; step S3, performing a third stirring on the first mixed solution, the second mixed solution and a dopant containing M to obtain a third mixed solution, and sequentially performing a second grinding, drying and sintering to obtain a modified lithium iron manganese phosphate material; wherein the hydrophobic agent includes one or more of octadecyl trichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyl triethoxysilane, tetraethoxysilane and polyacrylamide; M is niobium and / or aluminum. The modified lithium iron manganese phosphate material obtained by the above preparation method contains a hydrophobic group, has good hydrophobic properties, can effectively avoid the problem of excessive moisture caused by contact with air during subsequent processing and preparation, and has a stable structure and high cycle stability. In addition, the formation of the carbon layer and the doping of M ions can effectively improve the lithium ion diffusion coefficient and electronic conductivity.

[0010] Further, in step S1, the pretreatment is carried out in an air and / or nitrogen gas atmosphere; more preferably, the gas flow rate in the gas atmosphere is 0.3-0.5 L / min; and / or the pretreatment time is 30-40 s; and / or the first stirring includes the following steps: first adding a first solvent to the pretreated carbon source for a first sub-stirring, and then adding a hydrophobic agent for a second sub-stirring; preferably, the first sub-stirring time is 2-4 h; and / or the second sub-stirring time is 3-4 h; and / or the stirring speed is 200-300 rpm; and / or the photochemical reaction time is 0.5-2 h, and the temperature is 40-60 ° C; preferably, the photochemical reaction method includes one or more of infrared radiation method, electromagnetic radiation method and infrared laser method. Under the above conditions, there are more active groups on the surface of the carbon source, the modification and grafting reaction of the carbon source proceeds more fully, and more organic carbon chains are grafted to the modified carbon source. On the one hand, it is more conducive to tightly encapsulating the lithium iron manganese phosphate precursor, which is further beneficial to improving the stability of the structure of the modified lithium iron manganese phosphate material and reducing the particle size of the material. On the other hand, it is more conducive to improving the hydrophobicity of the modified lithium iron manganese phosphate material. In addition, the increasingly abundant branched structure can further improve the electronic conductivity of lithium iron manganese phosphate.

[0011] Further, in step S1, the carbon source includes one or more of glucose, polyacrylate, starch, PVA and PVDF; and / or the first solvent includes one or more of water, ethylene glycol, propanol, acetone and N-methylpyrrolidone; preferably, the first solvent includes water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is 1: (0.5-1), preferably 1: (0.5-0.6); and / or the hydrophobic agent includes octadecyltrichlorosilane and / or dodecanoic acid; preferably, when the hydrophobic agent is a mixture of octadecyltrichlorosilane and dodecanoic acid, the mass ratio of the two is (1-2): 1; and / or the mass ratio of the hydrophobic agent to the carbon source is (4-7): 100; and / or the mass ratio of the first solvent to the carbon source is 100: (42-65). Under the above conditions, the grafting effect of the carbon source is better and the hydrophobicity of the lithium manganese iron phosphate material is better.

[0012] Further, in step S2, a lithium source, an iron source, a manganese source, a phosphorus source, and a dopant are weighed respectively according to a stoichiometric ratio of Li:Fe:Mn:M:P of x:y:(1-yz):z:1, wherein 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; and / or the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium hydroxide; and / or the iron source includes one or more of ferric oxide, ferric phosphate, ferrous oxalate, ferrous oxide, and ferromanganese phosphate; and / or The manganese source includes one or more of ferromanganese phosphate, manganese carbonate and manganese tetraoxide; and / or the phosphorus source includes one or more of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate and ferromanganese phosphate; and / or the second solvent includes a polar solvent; and / or the mass ratio of the sum of the lithium source, manganese source, iron source, phosphorus source and the second solvent is (44-66):100; and / or the second stirring speed is 200-300rpm, and the time is 2-3h; and / or the first grinding is performed until the solid particle size in the second mixed solution is 800-1000nm. Under the above conditions, the compatibility of each raw material is better, and each raw material can cooperate with each other, which is more conducive to improving the electrochemical performance of lithium manganese iron phosphate.

[0013] Further, in step S3, the dopant includes niobium pentoxide and / or aluminum oxide; and / or the speed of the third stirring is 200-300rpm, and the time is 1-2h; and / or the second grinding is performed until the solid particle size in the third mixed solution is 350-420nm; and / or the drying temperature is 290-310℃; and / or the sintering includes the first sintering and the second sintering performed in sequence; preferably, the temperature of the first sintering is 750-790℃, and the time is 3-5h; the temperature of the second sintering is 670-710℃, and the time is 12-16h; preferably, the sintering atmosphere is argon and / or nitrogen, and the oxygen content in the atmosphere is less than 20ppm. Under the above conditions, it is more conducive to the preparation of modified lithium manganese iron phosphate material with fine particle size and uniform distribution, and the electrochemical performance of the modified lithium manganese iron phosphate is better.

[0014] According to another aspect of the present invention, a positive electrode material is provided, comprising the modified lithium manganese iron phosphate material, or comprising the modified lithium manganese iron phosphate material prepared according to the above preparation method. The positive electrode material of the present invention has a stable structure, strong hydrophobicity, excellent electronic conductivity and lithium ion diffusion coefficient, good charge and discharge performance, and long cycle life.

[0015] According to another aspect of the present invention, a lithium ion battery is provided, comprising the above-mentioned positive electrode material. The lithium ion battery of the present invention has a stable structure, strong hydrophobicity, excellent electronic conductivity and lithium ion diffusion coefficient, good charge and discharge performance, and long cycle life.

[0016] Compared with the prior art, the technical solution of the present invention has the following effects:

[0017] (1) The present invention adopts a hydrophobic agent to modify and graft the carbon source. The hydrophobic carbon source is curled during the preparation process, and the precursor of the lithium iron manganese phosphate material is tightly wrapped to form a stable core-shell structure. The hydrophobic carbon layer can support the overall structure of the lithium iron manganese phosphate, keep its own structure stable and not easily destroyed, which is beneficial to improving the stability of the lithium iron manganese phosphate structure, and can stabilize its own structure and not easily destroyed in the subsequent crushing process.

[0018] (2) The carbon chains of the hydrophobic agent are grafted onto the surface of the carbon source to form organic side chains. During the preparation of lithium manganese iron phosphate, the carbon source and the side chains are carbonized. The rich carbon chain structure is beneficial to improving the electron transmission efficiency, thereby improving the electronic conductivity and electrical conductivity of the lithium manganese iron phosphate material.

[0019] (3) The modified lithium manganese iron phosphate material of the present invention contains specific doping elements of niobium and / or aluminum. On the one hand, the doping elements can expand the lithium ion diffusion channel and reduce the energy barrier of lithium ion transmission; on the other hand, the addition of doping elements can make the lithium manganese iron phosphate material highly oriented, the grains slender, and form an ordered superlattice structure. The highly oriented grains can effectively inhibit the increase of internal resistance and improve the capacity retention rate of the material. The superlattice structure can also effectively inhibit the collapse of the crystal structure during charging and discharging, forming defects and holes inside the crystal, thereby changing the electronic structure of the material and improving the electronic conductivity of the material.

[0020] (4) The lithium iron manganese phosphate material is modified by using a hydrophobic agent to form a hydrophobic structure on its surface, so that the hydrophobicity of the lithium iron manganese phosphate material is significantly improved, which is conducive to solving the problem of excessive water content in the lithium iron manganese phosphate material during the preparation process, and can further effectively improve the electrochemical properties of the lithium iron manganese phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1 The TEM image of the modified lithium manganese iron phosphate material according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0024] As described in the background technology of the present invention, the prior art has the problems of poor structural stability, low electronic conductivity, low lithium ion diffusion coefficient, and excessive moisture during the preparation process, resulting in poor electrochemical performance. In order to solve the above problems, in a typical embodiment of the present invention, a modified lithium iron manganese phosphate material is provided. The modified lithium iron manganese phosphate material of the present invention includes a core and a hydrophobic carbon layer coated on the surface of the core, and the core includes a lithium iron manganese phosphate material, and its general formula is Li x Fe y Mn 1-y-z M z PO4, 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; M is niobium and / or aluminum; the raw material of the hydrophobic carbon layer is a carbon source modified by a hydrophobic agent; the hydrophobic agent includes one or more of octadecyltrichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyltriethoxysilane, tetraethoxysilane and polyacrylamide.

[0025] In the prior art, during the preparation of lithium manganese iron phosphate, the carbon source is in the presence of a dispersant (such as glucose in water as a dispersant), and the molecular chain exists in an extended conformation, wherein the polar groups are evenly distributed along the molecular chain, resulting in a loose carbon layer obtained after carbonization, and a poor wrapping effect on the lithium manganese iron phosphate particles. During the charge and discharge process, as lithium ions are released and embedded, the volume of the lithium manganese iron phosphate crystals continues to change, and the structural integrity is destroyed. As the cycle proceeds, the electrical performance of the lithium manganese iron phosphate deteriorates severely.

[0026] The modified lithium iron manganese phosphate material of the present invention includes a core and a hydrophobic carbon layer coated on the surface of the core, the core includes the lithium iron manganese phosphate material, and the raw material of the hydrophobic carbon layer is a carbon source modified by a specific type of hydrophobic agent of the present invention. The inventor unexpectedly found in a large number of experiments that the carbon source is modified and grafted with a hydrophobic agent, and the carbon source is grafted with a hydrophobic group. During the preparation process, the stretched carbon source molecular chain in the hydrophobic carbon source is curled, and the precursor of the lithium iron manganese phosphate material is tightly wrapped to form a stable core-shell structure. The hydrophobic carbon layer can support the overall structure of the lithium iron manganese phosphate, keep its own structure stable, and not easily cause structural collapse during the charge and discharge cycle, thereby effectively improving the cycle efficiency of the lithium iron manganese phosphate. On the other hand, the carbon source molecular chain tightly wraps the precursor of the lithium iron manganese phosphate material, and also makes the particle size of the modified lithium iron manganese phosphate particles smaller, and the carbon layer becomes tighter, so that the conductive effect of the lithium iron manganese phosphate is effectively improved.

[0027] In addition, the carbon chains of the hydrophobic agent are grafted on the surface of the carbon source to form organic side chains. During the preparation of lithium manganese iron phosphate, the carbon source and the side chains are carbonized. The rich carbon chain structure is beneficial to improving the electron transmission efficiency, thereby helping to improve the electronic conductivity and electrical conductivity of the lithium manganese iron phosphate material.

[0028] It should be noted that the present invention specifically uses the above-mentioned type of hydrophobic agent to modify the carbon source so that the surface of the modified lithium iron manganese phosphate material contains a hydrophobic structure, which significantly improves the hydrophobicity of the lithium iron manganese phosphate material, thereby helping to solve the problem of excessive moisture in the lithium iron manganese phosphate material during the preparation process, and further effectively improving the electrochemical properties of the lithium iron manganese phosphate material.

[0029] In addition, the modified lithium iron manganese phosphate material of the present invention contains specific doping elements of niobium and / or aluminum. On the one hand, the doping elements can expand the lithium ion diffusion channel and reduce the energy barrier of lithium ion transmission, thereby effectively improving the lithium ion diffusion coefficient; on the other hand, the addition of doping elements can make the lithium iron manganese phosphate material highly oriented, the grains slender, and form an ordered superlattice structure. The highly oriented grains can effectively inhibit the increase of internal resistance and improve the capacity retention rate of the material. The superlattice structure can also effectively inhibit the collapse of the crystal structure during charging and discharging, and form defects and holes inside the crystal, thereby changing the electronic structure of the material and improving the electronic conductivity of the material.

[0030] In the prior art, the smaller the particle size of lithium iron manganese phosphate, the shorter the path and faster the speed of lithium ions transferring from lithium iron manganese phosphate crystals, and the better its electrochemical performance. However, the smaller the particle size, the larger the specific surface area and the easier it is to absorb water. In order to prevent the material from absorbing water, the particle size of lithium iron manganese phosphate can generally only be set in a larger range (such as 480-600nm). Since the modified lithium iron manganese phosphate material of the present invention includes a hydrophobic carbon layer, the carbon source molecular chain tightly wraps the precursor of the lithium iron manganese phosphate material, making the modified lithium iron manganese phosphate particles smaller in particle size and the carbon layer more compact. In a preferred embodiment, the D50 particle size of the modified lithium iron manganese phosphate material is 350-420nm. On the basis of ensuring the hydrophobicity of the lithium iron manganese phosphate material, by controlling the material particle size within the above-mentioned small particle size range, the transfer path of lithium ions can be more effectively shortened and its transfer speed can be increased, thereby further improving the electrochemical performance of the lithium iron manganese phosphate material.

[0031] In a preferred embodiment, the mass ratio of the core to the carbon source is 100:(5.2-6.2). Under the above conditions, the core and the carbon source can cooperate with each other, and under the reduction reaction conditions, the carbon source can tightly wrap the core without affecting the deintercalation of lithium ions, stably support the overall structure of lithium iron manganese phosphate, provide a more sufficient conductive channel, and be more conducive to improving the conductive properties of the lithium iron manganese phosphate material, thereby making the stability, hydrophobicity, and electrochemical properties of the lithium iron manganese phosphate material better.

[0032] In another typical embodiment of the present invention, a preparation method of the modified lithium manganese iron phosphate material is also provided, comprising the following steps: step S1, pretreating a carbon source to obtain a pretreated carbon source, and subjecting the pretreated carbon source to a first stirring and photochemical reaction with a first solvent and a hydrophobic agent to obtain a first mixed solution containing a modified carbon source; step S2, sequentially subjecting a lithium source, an iron source, a manganese source, a phosphorus source and a second solvent to a second stirring and a first grinding to obtain a second mixed solution; step S3, subjecting the first mixed solution, the second mixed solution and a dopant containing M to a third stirring to obtain a third mixed solution, and sequentially subjecting the second grinding, drying and sintering to obtain a modified lithium manganese iron phosphate material; wherein the hydrophobic agent comprises one or more of octadecyltrichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyltriethoxysilane, tetraethoxysilane and polyacrylamide; and M is niobium and / or aluminum.

[0033] In the preparation method of the present invention, the carbon source is first pretreated to increase the active groups in the carbon source, to create conditions for the introduction of hydrophobic groups, and then the pretreated carbon source and the solvent and the hydrophobic agent are stirred and photochemically reacted. The hydrophobic agent is decomposed in the process, and the hydrophobic group in the hydrophobic agent is grafted to the carbon source side chain to obtain a first mixed solution containing a modified carbon source. Then, the lithium source, iron source, manganese source, phosphorus source and the second solvent are stirred and ground so that the lithium source, iron source, manganese source and phosphorus source are evenly distributed, and the obtained second mixed solution is stirred and ground with the dopant and the first mixed solution so that each material is evenly dispersed and fully contacted. In the third mixed solution, the modified carbon source is curled, and the precursor of the lithium iron manganese phosphate material is tightly wrapped, and the core-shell structure is stable and not easily destroyed, which is beneficial to improve the stability of the lithium iron manganese phosphate structure, and further beneficial to improve the cycle life of the lithium iron manganese phosphate material. Finally, drying, granulation and sintering are carried out. During the sintering process, based on the principle of high-valent metal doping, the doping of M effectively reduces the diffusion energy barrier of lithium ions, which is beneficial to promote the migration of lithium ions, reduce the band gap energy, improve the electronic conductivity, and promote the recombination of electrons and holes. The modified lithium manganese iron phosphate material obtained includes a lithium manganese iron phosphate core and a carbon layer coated outside the core, and the carbon layer contains hydrophobic groups.

[0034] The modified lithium manganese iron phosphate material obtained by the above preparation method contains hydrophobic groups and has good hydrophobic properties. It can effectively avoid the problem of excessive moisture caused by contact with air during subsequent processing and preparation, and has a stable structure and high cycle stability. In addition, the formation of the carbon layer and the doping of M ions can effectively improve the lithium ion diffusion coefficient and electronic conductivity.

[0035] In a preferred embodiment, in step S1, the pretreatment includes plasma treatment; preferably, the plasma treatment is carried out in an air and / or nitrogen gas atmosphere; more preferably, the gas flow rate in the gas atmosphere is 0.3-0.5 L / min; and / or the power of the plasma treatment is 50-70 W; and / or the time of the plasma treatment is 30-40 s. Under the above conditions, the number of active groups on the surface of the carbon source is greater, which is more conducive to the grafting reaction with the hydrophobic agent, and more organic carbon chains are grafted to the modified carbon source. On the one hand, it is more conducive to tightly coating the lithium iron manganese phosphate precursor, which is further conducive to improving the stability of the structure of the modified lithium iron manganese phosphate material and reducing the particle size of the material. On the other hand, it is more conducive to improving the hydrophobicity of the modified lithium iron manganese phosphate material. In addition, the increasingly abundant branched structure can further improve the electronic conductivity of the lithium iron manganese phosphate.

[0036] In a preferred embodiment, in step S1, the first stirring includes the following steps: first adding a first solvent to the pretreated carbon source for a first stirring, and then adding a hydrophobic agent for a second stirring; preferably, the first stirring time is 2 to 4 hours; and / or the second stirring time is 3 to 4 hours. Under the above conditions, the pretreated carbon source is first stirred with the solvent to dissolve the carbon source in the solvent, and then stirred with the hydrophobic agent to dissolve the hydrophobic agent, so that the modification grafting reaction of the carbon source can proceed more fully.

[0037] In a preferred embodiment, in step S1, the speed of the first stirring is 200-300 rpm. Under the above conditions, the distribution of the pretreated carbon source, the hydrophobic agent and the first solvent is more uniform, the contact is more complete, and the modification grafting reaction is more favorable.

[0038] In order to be more conducive to the modified grafting reaction, in a preferred embodiment, in step S1, the time of the photochemical reaction is 0.5 to 2 hours, and the temperature is 40 to 60°C; preferably, the photochemical reaction method includes one or more of infrared radiation method, electromagnetic radiation method and infrared laser method. The conditions of the above-mentioned photochemical reaction are simple, easy to control, and have few processes. If the reaction time is too long, it is easy to cause the solvent to evaporate quickly, causing abnormal material discharge during the spraying process, and, as the solvent evaporates, some hydrophobic agents may precipitate abnormally, which can easily lead to insufficient reaction. If the reaction time is too short, it may result in incomplete grafting, and some groups are not completely detached, so that the hydrophobic properties of the carbon source cannot be effectively improved.

[0039] In order to make the carbon source more tightly wrap the lithium iron manganese phosphate precursor in the solvent, it is more conducive to the preparation of a modified lithium iron manganese phosphate material with stable structure. In a preferred embodiment, in step S1, the carbon source includes one or more of glucose, polyacrylate, starch, PVA and PVDF; and / or the first solvent includes one or more of water, ethylene glycol, propanol, acetone and N-methylpyrrolidone; preferably, the first solvent includes water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is 1: (0.5-1), preferably 1: (0.5-0.6), and more preferably, when the first solvent includes water and ethylene glycol, in step S1, when adding the first solvent, water is added first, and then ethylene glycol is added. The solvent component under the above conditions acts as a dispersant, which can further increase the degree of curling of the carbon chain of the carbon source, so that the lithium iron manganese phosphate precursor and the carbon source can more fully form a shell-core structure, thereby more effectively improving the structural stability of the modified lithium iron manganese phosphate and reducing its particle size.

[0040] In order to further improve the grafting effect on the carbon source and thus further improve the hydrophobicity of the lithium manganese iron phosphate material, in a preferred embodiment, in step S1, the hydrophobic agent includes octadecyltrichlorosilane and / or dodecanoic acid; preferably, when the hydrophobic agent is a mixture of octadecyltrichlorosilane and dodecanoic acid, the mass ratio of the two is (1-2):1.

[0041] In order to allow the raw materials to fully contact and react, thereby being more conducive to improving the carbon source grafting modification effect, in a preferred embodiment, in step S1, the mass ratio of the hydrophobic agent to the carbon source is (4-7):100; and / or the mass ratio of the first solvent to the carbon source is 100:(42-65).

[0042] In a preferred embodiment, in step S2, lithium source, iron source, manganese source, phosphorus source, and dopant are weighed respectively according to the stoichiometric ratio of Li:Fe:Mn:M:P of x:y:(1-yz):z:1, wherein 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; and / or the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium hydroxide; and / or the iron source includes one or more of ferric oxide, ferrous phosphate, ferrous oxalate, ferrous oxide, and ferromanganese phosphate; and / or the manganese source includes one or more of ferromanganese phosphate, manganese carbonate, and manganese tetraoxide; and / or the phosphorus source includes one or more of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate, and ferromanganese phosphate. The above raw materials are low in price and widely available, and the raw materials can cooperate with each other, which is more conducive to improving the electrochemical performance of lithium iron manganese phosphate.

[0043] In order to make the contact between the lithium source, iron source, manganese source and phosphorus source more complete and their solubility in the solvent better, in a preferred embodiment, in step S2, the second solvent includes a polar solvent, preferably water; and / or the sum of the lithium source, manganese source, iron source and phosphorus source, and the mass ratio of the second solvent is (44-66):100.

[0044] Based on similar reasons, in a preferred embodiment, in step S2, the second stirring speed is 200-300 rpm, and the time is 2-3 h.

[0045] In order to make the particle size of the modified lithium manganese iron phosphate material smaller and the electrochemical performance better, in a preferred embodiment, the first grinding is performed until the particle size of the solid particles in the second mixed solution is 800-1000 nm.

[0046] In a preferred embodiment, in step S3, the dopant includes niobium pentoxide and / or aluminum oxide. Under the above conditions, it is more conducive to improving the lithium ion diffusion coefficient of the modified lithium manganese iron phosphate, and further more conducive to improving the electrochemical performance of the modified lithium manganese iron phosphate.

[0047] In a preferred embodiment, in step S3, the third stirring speed is 200-300 rpm, and the time is 1-2 hours; and / or the second grinding is performed until the solid particle size in the third mixed solution is 350-420 nm. Under the above conditions, the materials can be more fully contacted, which is more conducive to the preparation of modified lithium manganese iron phosphate material with fine particle size and uniform distribution.

[0048] In order to make the solvent evaporate more fully and the solid materials disperse more fully and evenly, in a preferred embodiment, in step S3, the drying temperature is 290-310°C.

[0049] In a preferred embodiment, in step S3, sintering includes a first sintering and a second sintering performed in sequence; preferably, the temperature of the first sintering is 750-790°C and the time is 3-5h; the temperature of the second sintering is 670-710°C and the time is 12-16h; preferably, the sintering atmosphere is argon and / or nitrogen, and the oxygen content in the atmosphere is less than 20ppm. In the first sintering process at a relatively high temperature, a crystal nucleus can be formed, and in the second sintering process at a relatively low temperature, it is conducive to grain growth. If the temperature of the first sintering is too low or the time is too short, it is not conducive to the growth of the crystal nucleus. If the first sintering temperature is too high or the time is too long, it is easy to cause excessive growth of the crystal nucleus, making the particle size of the modified lithium manganese iron phosphate material larger. If the temperature of the second sintering is too low or the time is too short, it is not conducive to the formation of grains. If the temperature of the second sintering is too high or the time is too long, the grain size will grow excessively, resulting in an excessively large particle size.

[0050] In another typical embodiment of the present invention, a positive electrode material is also provided, including the modified lithium manganese iron phosphate material, or including the modified lithium manganese iron phosphate material prepared according to the above preparation method. The positive electrode material of the present invention has a stable structure, strong hydrophobicity, excellent electronic conductivity and lithium ion diffusion coefficient, good charge and discharge performance, and long cycle life.

[0051] In another typical embodiment of the present invention, a lithium ion battery is provided, comprising the above-mentioned positive electrode material. The lithium ion battery of the present invention has a stable structure, strong hydrophobicity, excellent electronic conductivity and lithium ion diffusion coefficient, good charge and discharge performance, and long cycle life.

[0052] Typically but not limiting, in the modified lithium manganese iron phosphate material, the mass ratio of the core to the carbon source is 100:5.2, 100:5.5, 100:6, 100:6.2 or a range consisting of any two of them.

[0053] Typically but not limiting, in the first solvent, the volume ratio of water to ethylene glycol is 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range consisting of any two of them.

[0054] Typically but not limiting, the mass ratio of the hydrophobic agent to the carbon source is 4:100, 5:100, 6:100, 7:100 or a range consisting of any two of them.

[0055] Typically but not limiting, the mass ratio of the first solvent to the carbon source is 100:42, 100:45, 100:50, 100:55, 100:60, 100:65 or a range consisting of any two of them.

[0056] Typically but not limiting, the temperature of the first sintering is 750°C, 770°C, 790°C or a range consisting of any two of their values, and the time is 3h, 4h, 5h or a range consisting of any two of their values; the temperature of the second sintering is 670°C, 690°C, 710°C or a range consisting of any two of their values, and the time is 12h, 14h, 16h or a range consisting of any two of their values, and the oxygen content in the sintering atmosphere is less than 20ppm.

[0057] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0058] Example 1

[0059] The hydrophobic agent is octadecyltrichlorosilane and dodecanoic acid (the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 1.5:1); the mass ratio of the total amount of the hydrophobic agent to the carbon source is 5.5:100.

[0060] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 30 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 300 rpm for 2 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 100:53, and the volume ratio of the first part of water to ethylene glycol is 1:0.75), and stirring for 60 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 50° C. for 30 minutes; then adding dodecanoic acid, stirring for 2 hours, and maintaining at a temperature of 45° C. for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0061] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.3:0.696:0.004:1, weigh a lithium source (type is lithium dihydrogen phosphate), an iron source (type is iron phosphate), a manganese source (type is manganese tetroxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 55:100), stir at a speed of 300 rpm for 3 hours, and after uniformity, perform ultrafine grinding in an ultrafine grinder at a speed of 1900 rpm to obtain a second mixed solution, wherein the particle size of the solid particles is 1000 nm;

[0062] Step S3, add the dopant and the first mixed solution (the mass percentage of the first mixed solution in the third mixed solution is 15%) to the second mixed solution, continue stirring at 300rpm for 2h, perform ultrafine grinding in a sand mill, the rotation speed is 1900rpm, the solid particle size in the third mixed solution is 400nm, spray dry at 300°C, and then sinter under argon conditions (oxygen content is less than 20ppm), the first sintering temperature during the sintering process is 770°C, the time is 5h, the second sintering temperature is 690°C, and the time is 16h, to obtain a modified lithium manganese iron phosphate material.

[0063] The modified lithium manganese iron phosphate material includes a lithium manganese iron phosphate material core and a carbon layer containing hydrophobic groups. The hydrophobic groups are active silanols and carbon chains. The TEM image of the modified lithium manganese iron phosphate material is shown in Figure 1 .Depend on Figure 1 It can be seen that the lithium manganese iron phosphate particles are round without sharp edges, the carbon layer is tightly wrapped, and the thickness of the carbon layer is between 2-5nm.

[0064] Example 2

[0065] The only difference from Example 1 is:

[0066] In the hydrophobic agent, the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 2:1.

[0067] Example 3

[0068] The only difference from Example 1 is:

[0069] In the hydrophobic agent, the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 1:1.

[0070] Example 4

[0071] The only difference from Example 1 is:

[0072] The hydrophobic agent is octadecyltrichlorosilane.

[0073] Example 5

[0074] The only difference from Example 1 is:

[0075] The hydrophobic agent is dodecanoic acid.

[0076] Example 6

[0077] The only difference from Example 1 is:

[0078] The hydrophobic agent is oleic acid.

[0079] Example 7

[0080] The only difference from Example 1 is:

[0081] The hydrophobic agent is tridecafluorooctyltriethoxysilane.

[0082] Example 8

[0083] The only difference from Example 1 is:

[0084] The mass ratio of the total amount of the hydrophobic agent to the carbon source is 4:100.

[0085] Example 9

[0086] The only difference from Example 1 is:

[0087] The mass ratio of the total amount of the hydrophobic agent to the carbon source is 7:100.

[0088] Example 10

[0089] The only difference from Example 1 is:

[0090] In step S1, the types of carbon sources are different and the parameters in the pretreatment process are different, specifically:

[0091] Glucose was used as the carbon source, and the carbon source was treated in a plasma instrument for 30 seconds under the conditions of a nitrogen atmosphere, a gas flow rate of 0.5 L / min, and a plasma treatment power of 70 W to obtain a pretreated carbon source.

[0092] Embodiment 11

[0093] The only difference from Example 1 is:

[0094] In step S1, the types of carbon sources are different and the parameters in the pretreatment process are different, specifically:

[0095] Glucose was used as the carbon source, and the carbon source was treated in a plasma instrument for 40 seconds under the conditions of air atmosphere, gas flow rate of 0.3 L / min, and plasma treatment power of 50 W to obtain a pretreated carbon source.

[0096] Example 12

[0097] The only difference from Example 1 is:

[0098] In step S1, the first solvent type is different, and the parameters in the photochemical reaction process are different, specifically:

[0099] The pretreated carbon source is added to the first part of water, stirred at 300 rpm for 2 hours to dissolve it, added to N-methylpyrrolidone (the mass ratio of the sum of the first part of water and N-methylpyrrolidone to the carbon source is 100:42, and the volume ratio of the first part of water to N-methylpyrrolidone is 1:0.5), and stirred for 60 minutes; octadecyltrichlorosilane is continued to be added, and treated at 40°C for 60 minutes with infrared radiation; dodecanoic acid is added, stirred for 4 hours, and maintained at a temperature of 60°C for 2 hours to obtain a first mixed solution containing a modified carbon source.

[0100] Embodiment 13

[0101] The only difference from Example 1 is:

[0102] In step S1, the first solvent type is different, and the parameters in the photochemical reaction process are different, specifically:

[0103] The pretreated carbon source is added to the first part of water, stirred at 300 rpm for 2 hours to dissolve it, and propanol (the content is the sum of the first part of water and N-methylpyrrolidone, the mass ratio to the carbon source is 100:65, and the volume ratio of the first part of water to propanol is 1:0.6) is added and stirred for 60 minutes; octadecyltrichlorosilane is continued to be added, and treated at 50°C for 30 minutes using electromagnetic radiation; dodecanoic acid is then added, stirred for 2 hours, and maintained at a temperature of 45°C for 2 hours to obtain a first mixed solution containing a modified carbon source.

[0104] Embodiment 14

[0105] The only difference from Example 1 is:

[0106] In step S2, the types and contents of the lithium source, iron source, manganese source, phosphorus source, and the second solvent are different, specifically:

[0107] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.1:0.898:0.002:1, weigh a lithium source (lithium carbonate), an iron source (ferrous oxalate), a manganese source (manganese carbonate), a doping element (Nb2O5), and a phosphorus source (ammonium dihydrogen phosphate). The second solvent is the second part of water, and the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 66:100.

[0108] Embodiment 15

[0109] The only difference from Example 1 is:

[0110] In step S2, the types and contents of the lithium source, iron source, manganese source, phosphorus source, and the second solvent are different, specifically:

[0111] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.02:0.4:0.595:0.005:1, weigh a lithium source (lithium hydroxide), an iron source (ferrous oxide), a manganese source (manganese carbonate), a dopant (Nb2O5), and a phosphorus source (ammonium dihydrogen phosphate). The second solvent is the second part of water, and the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 44:100.

[0112] Example 16

[0113] The only difference from Example 1 is:

[0114] In step S3, the type of dopant is aluminum oxide.

[0115] Embodiment 17

[0116] The only difference from Example 1 is:

[0117] In step S3, the type of dopant is niobium pentoxide.

[0118] Embodiment 18

[0119] The only difference from Example 1 is:

[0120] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 30 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 200 rpm for 2 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 1:0.53, and the volume ratio of the first part of water to ethylene glycol is 1:0.75), and stirring for 60 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 60°C for 30 minutes; then adding dodecanoic acid, stirring for 3 hours, and maintaining at a temperature of 45°C for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0121] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.3:0.696:0.004:1, weigh a lithium source (type is lithium dihydrogen phosphate), an iron source (type is iron phosphate), a manganese source (type is manganese tetroxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 55:100), stir at a speed of 200 rpm for 3 hours, and then perform ultrafine grinding in a sand mill to obtain a second mixed solution, wherein the particle size of the solid particles is 800 nm;

[0122] Step S3, add the dopant and the first mixed solution to the second mixed solution, continue stirring at 200rpm for 1h, and then perform ultrafine grinding. The solid particle size in the third mixed solution is 420nm, spray drying is performed at an inlet air temperature of 290°C, and then sintering is performed under argon conditions (oxygen content is less than 20ppm). During the sintering process, the first sintering temperature is 780°C and the time is 5h. The second sintering temperature is 700°C and the time is 16h to obtain a modified lithium manganese iron phosphate material.

[0123] Embodiment 19

[0124] The only difference from Example 1 is:

[0125] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 30 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 300 rpm for 4 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 1:0.53, and the volume ratio of the first part of water to ethylene glycol is 1:0.75), and stirring for 60 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 40°C for 30 minutes; then adding dodecanoic acid, stirring for 4 hours, and maintaining at a temperature of 45°C for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0126] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.3:0.696:0.004:1, weigh a lithium source (type is lithium dihydrogen phosphate), an iron source (type is iron phosphate), a manganese source (type is manganese tetroxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 55:100), stir at a speed of 300rpm for 2h, and after uniformity, perform ultrafine grinding in a sand mill to obtain a second mixed solution, wherein the particle size of the solid particles is 1000nm;

[0127] Step S3, add the dopant and the first mixed solution to the second mixed solution, continue stirring at 300rpm for 2h, and then perform ultrafine grinding. The solid particle size in the third mixed solution is 350nm, spray drying is performed at an inlet air temperature of 310°C, and then sintering is performed under argon conditions (oxygen content is less than 20ppm). During the sintering process, the first sintering temperature is 780°C, the time is 5h, and the second sintering temperature is 700°C, and the time is 16h, to obtain a modified lithium manganese iron phosphate material.

[0128] Embodiment 20

[0129] The only difference from Example 1 is:

[0130] Step S3, during the sintering process, the first sintering temperature is 790° C., the time is 5 hours, and the second sintering temperature is 710° C., the time is 16 hours, to obtain a modified lithium manganese iron phosphate material.

[0131] Embodiment 21

[0132] The only difference from Example 1 is:

[0133] Step S3, during the sintering process, the first sintering temperature is 750° C., the time is 3 hours, and the second sintering temperature is 670° C., the time is 16 hours, to obtain a modified lithium manganese iron phosphate material.

[0134] Embodiment 22

[0135] The hydrophobic agent is octadecyltrichlorosilane and dodecanoic acid (the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 2:1); the mass ratio of the total amount of the hydrophobic agent to the carbon source is 5:100.

[0136] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 40 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to water, stirring at 300 rpm for 3 hours to dissolve it, adding ethylene glycol (the sum of the first part of water and ethylene glycol, the mass ratio to the carbon source is 100:42, and the volume ratio of the first part of water to ethylene glycol is 1:0.6), and stirring for 30 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 50° C. for 60 minutes; then adding dodecanoic acid, stirring for 1 hour, and maintaining at a temperature of 45° C. for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0137] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.3:0.696:0.004:1, weigh a lithium source (type is lithium dihydrogen phosphate), an iron source (type is iron phosphate), a manganese source (type is manganese tetraoxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 55:100), stir at a speed of 300 rpm for 2 hours, and after uniformity, perform ultrafine grinding in an ultrafine grinder at a speed of 1900 rpm to obtain a second mixed solution, wherein the particle size of the solid particles is 1000 nm;

[0138] Step S3, add the dopant and the first mixed solution to the second mixed solution, continue stirring at 300rpm for 2h, and then perform ultrafine grinding. The solid particle size in the third mixed solution is 400nm, spray drying is performed at an inlet air temperature of 300°C, and then sintering is performed under argon conditions (oxygen content is less than 20ppm). During the sintering process, the first sintering temperature is 780°C, the time is 5h, and the second sintering temperature is 670°C, and the time is 16h, to obtain a modified lithium manganese iron phosphate material.

[0139] Embodiment 23

[0140] The hydrophobic agent is octadecyltrichlorosilane and dodecanoic acid (the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 1:1); the mass ratio of the total amount of the hydrophobic agent to the carbon source is 4:100.

[0141] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 30 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 300 rpm for 2 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 100:50, and the volume ratio of the first part of water to ethylene glycol is 1:0.5), and stirring for 60 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 50° C. for 30 minutes; then adding dodecanoic acid, stirring for 2 hours, and maintaining at a temperature of 60° C. for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0142] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.01:0.3:0.698:0.002:1, weigh a lithium source (type is lithium hydroxide), an iron source (type is iron phosphate), a manganese source (type is manganese tetraoxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 66:100), stir at a speed of 300 rpm for 3 hours, and after uniformity, perform ultrafine grinding in an ultrafine grinder to obtain a second mixed solution, wherein the particle size of the solid particles is 1000 nm;

[0143] Step S3, add the dopant and the first mixed solution to the second mixed solution, continue stirring at 300 rpm for 2 hours, and then perform ultrafine grinding. The solid particle size in the third mixed solution is 420 nm, and spray drying is performed at an inlet air temperature of 310°C, and then granulation and sintering are performed. During the sintering process under argon conditions (oxygen content is less than 20 ppm), the first sintering temperature is 750°C, the time is 3 hours, and the second sintering temperature is 670°C, and the time is 12 hours to obtain modified lithium manganese iron phosphate material.

[0144] Embodiment 24

[0145] The hydrophobic agent is octadecyltrichlorosilane and dodecanoic acid (the mass ratio of octadecyltrichlorosilane to dodecanoic acid is 1:1); the mass ratio of the total amount of the hydrophobic agent to the carbon source is 6:100.

[0146] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 40 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 200 rpm for 2 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 100:65, and the volume ratio of the first part of water to ethylene glycol is 1:0.8), and stirring for 60 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 50° C. for 60 minutes; then adding dodecanoic acid, stirring for 1 hour, and maintaining at a temperature of 45° C. for 4 hours to obtain a first mixed solution containing a modified carbon source;

[0147] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.02:0.1:0.898:0.002:1, weigh a lithium source (type is lithium dihydrogen phosphate), an iron source (type is iron phosphate), a manganese source (type is manganese tetraoxide), a dopant (type is Nb2O5), and a phosphorus source (type is iron phosphate), add the lithium source, iron source, manganese source, and phosphorus source to a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, manganese source, iron source, and phosphorus source to the second part of water is 44:100), stir at a speed of 200 rpm for 3 hours, and after uniformity, perform ultrafine grinding in an ultrafine grinder to obtain a second mixed solution, wherein the particle size of the solid particles is 800 nm;

[0148] Step S3, add the dopant and the first mixed solution to the second mixed solution, continue stirring at 200rpm for 2h, and then perform ultrafine grinding. The solid particle size in the third mixed solution is 420nm, and spray drying is performed at an inlet air temperature of 300°C, and then granulation and sintering are performed. During the sintering process under argon conditions (oxygen content is less than 20ppm), the first sintering temperature is 750°C, the time is 3h, and the second sintering temperature is 710°C, and the time is 12h, to obtain a modified lithium manganese iron phosphate material.

[0149] In a glove box filled with argon atmosphere, the prepared modified lithium manganese iron phosphate material is used as the positive electrode material, graphite is used as the negative electrode, and the battery shell is encapsulated to isolate the air to assemble a lithium-ion battery.

[0150] Embodiment 25

[0151] The hydrophobic agent is dodecanoic acid; the mass ratio of the total amount of the hydrophobic agent to the carbon source is 5:100.

[0152] Step S1, using glucose as a carbon source, treating the carbon source in a plasma instrument for 40 seconds under the conditions of an air atmosphere, a gas flow rate of 0.4 L / min, and a plasma treatment power of 60 W to obtain a pretreated carbon source; adding the pretreated carbon source to the first part of water, stirring at 200 rpm for 3 hours to dissolve it, adding ethylene glycol (the mass ratio of the sum of the first part of water and ethylene glycol to the carbon source is 100:60, and the volume ratio of the first part of water to ethylene glycol is 1:1), and stirring for 30 minutes; continuing to add octadecyltrichlorosilane, irradiating with infrared light, and treating at 50° C. for 60 minutes; then adding dodecanoic acid, stirring for 1 hour, and maintaining at a temperature of 60° C. for 2 hours to obtain a first mixed solution containing a modified carbon source;

[0153] Step S2, according to the stoichiometric ratio of Li:Fe:Mn:M:P=1.02:0.2:0.795:0.005:1, weigh a lithium source (type is lithium carbonate), an iron source (type is ferric phosphate), a manganese source (type is manganese tetraoxide), a dopant (type is Nb2O5), and a phosphorus source (type is manganese iron phosphate), add a second solvent (type is the second part of water, the mass ratio of the sum of the lithium source, the manganese source, the iron source, and the phosphorus source to the second part of water is 45:100), stir at a speed of 200 rpm for 2 hours, and after uniformity, perform ultrafine grinding in an ultrafine grinder at a speed of 1800 rpm to obtain a second mixed solution, wherein the particle size of the solid particles is 800 nm;

[0154] Step S3, adding dopant to the second mixed solution, the first mixed solution, continuing to stir at 200rpm for 2h, and then ultrafine grinding, the rotation speed is 1800rpm, the solid particle size in the third mixed solution is 400nm, spray drying is carried out at an inlet air temperature of 310°C, and then granulation and sintering are carried out. During the sintering process under argon conditions (oxygen content is less than 20ppm), the first sintering temperature is 750°C, the time is 3h, and the second sintering temperature is 710°C, the time is 12h, and modified lithium manganese iron phosphate material is obtained.

[0155] Comparative Example 1

[0156] The only difference from Example 1 is:

[0157] No pretreatment or modification of the carbon source was performed.

[0158] Comparative Example 2

[0159] The only difference from Example 1 is:

[0160] The mass ratio of the hydrophobic agent to the carbon source is 9:100.

[0161] Comparative Example 3

[0162] The only difference from Example 1 is:

[0163] The mass ratio of the hydrophobic agent to the carbon source is 3:100.

[0164] Comparative Example 4

[0165] The only difference from Example 1 is:

[0166] The hydrophobic agent is replaced with water.

[0167] Comparative Example 5

[0168] The only difference from Example 1 is:

[0169] In step S1, the carbon source is treated in a plasma instrument for 40 seconds; treated at 45° C. for 60 minutes under infrared light radiation; and stirred for 1 hour after adding dodecanoic acid.

[0170] Comparative Example 6

[0171] CN 116354328 A。

[0172] Comparative Example 7

[0173] The only difference from Example 1 is:

[0174] The dopant is vanadium pentoxide.

[0175] In a glove box filled with argon atmosphere, the prepared modified lithium manganese iron phosphate material is used as the positive electrode material, graphite is used as the negative electrode, and the battery shell is encapsulated to isolate the air to assemble a lithium-ion battery.

[0176] The D50 particle size, electronic conductivity, lithium ion diffusion coefficient, and electrochemical performance test results of the modified lithium manganese iron phosphate prepared in the above examples and comparative examples are shown in Table 1.

[0177] Test method:

[0178] D50 particle size: tested by laser particle size analyzer, ultrasonic time 20-60s;

[0179] Lithium ion diffusion coefficient: tested by constant current intermittent titration method under the conditions of current 0.2C, voltage 2.0~4.5V, temperature 25℃, humidity 40RH%;

[0180] Charge and discharge performance test: Test 0.2C discharge capacity and 1C discharge capacity at 2.0-4.5V and 25℃;

[0181] Cycle performance: Capacity retention after 200 cycles at 25°C, 2.0-4.5V, 1C.

[0182] Table 1

[0183]

[0184]

[0185] Compared with the unmodified carbon source in comparative example 1, the capacity of the lithium manganese iron phosphate material is slightly improved by using the modified carbon source of the present invention, and the cycle retention rate and lithium ion diffusion coefficient are significantly improved. Compared with comparative example 8, the addition of the specific doping element of the present invention significantly improves the lithium ion diffusion effect.

[0186] It can be seen from the above that compared with the comparative example, the embodiments of the present invention can effectively solve the problems of poor structural stability, low electronic conductivity, low lithium ion diffusion coefficient, and excessive moisture in the preparation process, resulting in poor electrochemical performance of the lithium iron manganese phosphate material by controlling the raw materials and types of doping elements of the hydrophobic carbon layer in the modified lithium iron manganese phosphate material.

[0187] Specifically, the present invention adopts a hydrophobic agent to modify and graft the carbon source. The hydrophobic carbon source is curled during the preparation process, and the precursor of the lithium iron manganese phosphate material is tightly wrapped to form a stable core-shell structure. The hydrophobic carbon layer can support the overall structure of the lithium iron manganese phosphate, keep its own structure stable and not easily destroyed, which is beneficial to improve the stability of the lithium iron manganese phosphate structure, and can stabilize its own structure and not easily destroyed in the subsequent crushing process.

[0188] Secondly, the carbon chains of the hydrophobic agent are grafted on the surface of the carbon source to form organic side chains. During the preparation of lithium manganese iron phosphate, the carbon source and the side chains are carbonized. The rich carbon chain structure is beneficial to improving the electron transmission efficiency, thereby helping to improve the electronic conductivity and electrical conductivity of the lithium manganese iron phosphate material.

[0189] In addition, the modified lithium manganese iron phosphate material of the present invention contains specific doping elements of niobium and / or aluminum. On the one hand, the doping elements can expand the lithium ion diffusion channel and reduce the energy barrier of lithium ion transmission; on the other hand, the addition of doping elements can make the lithium manganese iron phosphate material highly oriented, the grains slender, and form an ordered superlattice structure. The highly oriented grains can effectively inhibit the increase of internal resistance and improve the capacity retention rate of the material. The superlattice structure can also effectively inhibit the collapse of the crystal structure during charging and discharging, and form defects and holes inside the crystal, thereby changing the electronic structure of the material and improving the electronic conductivity of the material.

[0190] Moreover, by using a hydrophobic agent to modify the lithium iron manganese phosphate material, a hydrophobic structure can be formed on its surface, which significantly improves the hydrophobicity of the lithium iron manganese phosphate material, thereby helping to solve the problem of excessive moisture in the lithium iron manganese phosphate material during the preparation process, and further effectively improving the electrochemical properties of the lithium iron manganese phosphate material.

[0191] In addition, it can be seen that when the process parameters are within the preferred range of the present invention, the particle size of the modified lithium manganese iron phosphate material is smaller and the electrochemical performance of the lithium ion battery is better.

[0192] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified lithium manganese iron phosphate material, characterized in that: It comprises a core and a hydrophobic carbon layer coated on the surface of the core, The core comprises lithium manganese iron phosphate material, the general formula of which is Li x Fe y Mn 1-y-z M z PO4, 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; M is niobium and / or aluminum; The raw material of the hydrophobic carbon layer is a carbon source modified by a hydrophobic agent; The hydrophobic agent includes one or more of octadecyltrichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyltriethoxysilane, tetraethoxysilane and polyacrylamide.

2. The modified lithium iron manganese phosphate material according to claim 1, characterized in that: The D50 particle size of the modified lithium manganese iron phosphate material is 350-420 nm.

3. The modified lithium iron manganese phosphate material according to claim 1 or 2, characterized in that: The mass ratio of the core to the carbon source is 100:(5.2-6.2).

4. The method for preparing the modified lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, pretreating a carbon source to obtain a pretreated carbon source, and subjecting the pretreated carbon source to a first stirring and photochemical reaction with a first solvent and a hydrophobic agent to obtain a first mixed solution containing a modified carbon source; Step S2, sequentially performing a second stirring and a first grinding on the lithium source, the iron source, the manganese source, the phosphorus source and the second solvent to obtain a second mixed solution; Step S3, performing a third stirring on the first mixed solution, the second mixed solution and the dopant containing M to obtain a third mixed solution, and sequentially performing a second grinding, drying and sintering to obtain the modified lithium manganese iron phosphate material; Wherein, the hydrophobic agent comprises one or more of octadecyltrichlorosilane, dodecanoic acid, oleic acid, tridecafluorooctyltriethoxysilane, tetraethoxysilane and polyacrylamide; and M is niobium and / or aluminum.

5. The preparation method according to claim 4, characterized in that: In the step S1, The pretreatment is carried out in an air and / or nitrogen gas atmosphere; More preferably, the flow rate of the gas in the gas atmosphere is 0.3 to 0.5 L / min; and / or The pretreatment time is 30 to 40 seconds; and / or The first stirring comprises the following steps: firstly adding the first solvent to the pretreated carbon source for first stirring, and then adding the hydrophobic agent for second stirring; preferably, the first stirring time is 2 to 4 hours; and / or the second stirring time is 3 to 4 hours; and / or the stirring speed is 200 to 300 rpm; and / or The photochemical reaction time is 0.5 to 2 hours, and the temperature is 40 to 60°C; Preferably, the photochemical reaction method includes one or more of infrared radiation method, electromagnetic radiation method and infrared laser method.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S1, The carbon source comprises one or more of glucose, polyacrylate, starch, PVA and PVDF; and / or The first solvent comprises one or more of water, ethylene glycol, propanol, acetone and N-methylpyrrolidone; preferably, the first solvent comprises water and ethylene glycol, wherein the volume ratio of water to ethylene glycol is 1:(0.5-1), preferably 1: (0.5~0.6); and / or The hydrophobic agent includes octadecyltrichlorosilane and / or dodecanoic acid; preferably, when the hydrophobic agent is a mixture of octadecyltrichlorosilane and dodecanoic acid, the mass ratio of the two is (1-2):1; and / or The mass ratio of the hydrophobic agent to the carbon source is (4-7):100; and / or The mass ratio of the first solvent to the carbon source is 100:(42-65).

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S2, The lithium source, the iron source, the manganese source, the phosphorus source, and the dopant are weighed respectively according to the stoichiometric ratio of Li:Fe:Mn:M:P of x:y:(1-yz):z:1, wherein 1.01≤x≤1.02, 0<y≤0.4, 0.002≤z≤0.005; and / or The lithium source comprises one or more of lithium carbonate, lithium dihydrogen phosphate, dilithium hydrogen phosphate and lithium hydroxide; and / or The iron source comprises one or more of ferric oxide, ferric phosphate, ferrous oxalate, ferrous oxide and ferromanganese phosphate; and / or The manganese source comprises one or more of ferromanganese phosphate, manganese carbonate and manganese tetraoxide; and / or The phosphorus source comprises one or more of lithium dihydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate and ferromanganese phosphate; and / or The second solvent comprises a polar solvent; and / or The mass ratio of the sum of the lithium source, the manganese source, the iron source, and the phosphorus source to the second solvent is (44-66):100; and / or The second stirring speed is 200-300 rpm, and the time is 2-3 hours; and / or The first grinding is performed until the particle size of solid particles in the second mixed solution is 800-1000 nm.

8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S3, The dopant comprises niobium pentoxide and / or aluminum oxide; and / or The third stirring speed is 200-300 rpm, and the time is 1-2 hours; and / or The second grinding is performed until the particle size of the solid particles in the third mixed solution is 350-420 nm; and / or The drying temperature is 290-310°C; and / or The sintering includes a first sintering and a second sintering performed sequentially; preferably, the temperature of the first sintering is 750-790°C and the time is 3-5 hours; the temperature of the second sintering is 670-710°C and the time is 12-16 hours; preferably, the sintering atmosphere is argon and / or nitrogen, and the oxygen content in the atmosphere is less than 20ppm.

9. A positive electrode material, characterized in that: The invention comprises the modified lithium iron manganese phosphate material according to any one of claims 1 to 3, or comprises the modified lithium iron manganese phosphate material prepared by the preparation method according to any one of claims 4 to 8.

10. A lithium ion battery, characterized in that: Comprising the positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation of ultra-hydrophobic polyvinylidene fluoride membrane and product thereof

    CN101463140A

  • Modified lithium-containing phosphate positive electrode material as well as preparation method and application thereof

    CN113594449A

  • Positive electrode material and lithium ion battery

    CN115763733A

  • High-performance lithium ferric manganese phosphate composite material as well as preparation method and application thereof

    CN116314693A

  • Lithium ferromanganese phosphate composite material and preparation thereof

    US20240092640A1

Cited By

  • Positive electrode material and preparation method therefor, positive electrode sheet, and lithium battery

    WO2026113231A1